Human microbiome signatures of differential colorectal cancer drug metabolism. (December 2017) - Guthrie, Leah; Gupta, Sanchit; Daily, Johanna; Kelly, Libusha
Abstract It is well appreciated that microbial metabolism of drugs can influence treatment efficacy. Microbial β-glucuronidases in the gut can reactivate the excreted, inactive metabolite of irinotecan, a first-line chemotherapeutic for metastatic colorectal cancer. Reactivation causes adverse drug responses, including severe diarrhea. However, a direct connection between irinotecan metabolism and the composition of an individual's gut microbiota has not previously been made. Here, we report quantitative evidence of inter-individual variability in microbiome metabolism of the inactive metabolite of irinotecan to its active form. We identify a high turnover microbiota metabotype with potentially elevated risk for irinotecan-dependent adverse drug responses. We link the high turnover metabotype to unreported microbial β-glucuronidases; inhibiting these enzymes may decrease irinotecan-dependent adverse drug responses in targeted subsets of patients. In total, this study reveals metagenomic mining of the microbiome, combined with metabolomics, as a non-invasive approach to develop biomarkers for colorectal cancer treatment outcomes. Bowel cancer: human gut microbes can metabolize drugs Differences in the microbial populations in the gut may help predict the likelihood of adverse reactions to a drug used to treat bowel cancer. Libusha Kelly, Leah Guthrie, and colleagues at Albert Einstein College of Medicine in New York examined the undesirable reactivation of the chemotherapy drug irinotecan by microbial enzymes in the gut. They identified an association between specific forms of microbial metabolic activity and drug metabolism. Sampling the microbial population of a patient's gut may therefore offer a relatively non-invasive way to identify biomarkers predicting the likelihood of adverse reactions due to microbial metabolism. The research also suggests that using drugs to inhibit the activity of specific microbial enzymes in the gut might improve the outcome of some treatments. Modifying the microbial population prior to treatment may be another option.